Differentiating pediatric cystic nephroma from common renal multicystic lesions: A case report - Jun Zhou; Lv Meng-Xing; Ling Duan; Yan Gao (Wolters Kluwer Medknow Publications, 2022)
Pediatric cystic nephroma is a rare, clinically benign, renal tumor. Pediatric renal cystic lesions are complex. Imaging findings and tumor appearance are often nonspecific, and careful pathological examination is necessary. We discuss diagnosis of pediatric cystic nephroma and how to differentiate it from multicystic dysplastic kidney and cystic partially differentiated nephroblastoma.